(untitled) (Homoeopathy for All, 2024)
The quintessential teacher embodies a spectrum of roles, extending well beyond the confines of classroom instructions. Such an educator not only imparts academic knowledge but also instils ethical principles within students. Educators bear a significant moral obligation to keep parents informed about their children’s academic performances. Given the high esteem the society holds for teachers, it is incumbent upon them to strive to meet these societal expectations and vice versa.